Risk factors of postoperative nausea and vomiting after total hip arthroplasty or total knee arthroplasty: a retrospective study - Wang, Yingjie (Ann Transl Med, 2020)
BACKGROUND: Postoperative nausea and vomiting (PONV) is a common complication after total hip/knee arthroplasty (THA/TKA) that affects patient satisfaction and postoperative recovery. It has been reported that patients undergoing THA/TKA experience PONV at a frequency of 20–83%. This study investigates the occurrence of PONV in patients and analyzes the risk factors. METHODS: Patients undergoing primary THA/TKA under general anesthesia from October 1, 2017, to May 1, 2018, were included. Data on patient-related factors were collected before THA/TKA. Anesthesia- and surgery-related factors were recorded postoperatively. Risk factors were analyzed using binary logistic regression. RESULTS: A stronger association of motion sickness and PONV was found at six hours after bilateral THA/TKA [nausea: odds ratio (OR) =14.648, 3.939–54.470; vomiting: OR =8.405, 2.482–28.466]. At 6–24 hours after bilateral THA/TKA, patients who had a history of migraines tended to experience nausea (OR =12.589, 1.978–80.105). Patients with lower body mass index (BMI) were more likely to experience PONV at 24–72 hours (nausea: OR =0.767, 0.616–0.954; vomiting: OR =0.666, 0.450–0.983) after bilateral THA/TKA. CONCLUSIONS: The incidence of PONV after primary bilateral THA/TKA was higher than that after unilateral THA/TKA. The risk factors vary at different time points after surgery, and a history of motion sickness is the most critical factor affecting PONV.